PROBLEM PENEGAKAN HAK ASASI MANUSIA DI INDONESIA - A. Malthuf Siroj (JURNAL HAKAM, 2020)
The issue of human rights enforcement has always been an interesting spotlight in the public, including in Indonesia. This is because the existence of human rights is always attached to every human being. Besides that, guarantee and protection of human rights is also one of the benchmarks for the nation and state progress. The presence of this research is also inseparable from the efforts to answer various problems of human rights enforcement in Indonesia, which have so far been considered badly by Human Rights Watch (HRW) in the 2020 word report, especially for vulnerable groups. Therefore, this research not only presents a detailed description of the theoretical aspects of human rights itself, but also describes in detail the important instruments for human rights enforcement, various problems in enforcing human rights in Indonesia, as well as some important solutions that needs to be implemented immediately in the practice of human rights enforcement so that the manifestation of substantive truth and justice is truly felt by all levels of Indonesian society.Keywords: Human Rights Enforcement, Human Rights Problems, Human Rights Enforcement Solutions